Jellyfish aggregations and leatherback turtle foraging patterns in a temperate coastal environment - Houghton, Jonathan; Doyle, T.K.; Wilson, M.W.; Davenport, J.; Hays, G.C. (2006)
Leatherback turtles (Dermochelys coriacea) are obligate predators of gelatinous zooplankton. However, the spatial relationship between predator and prey remains poorly understood beyond sporadic and localized reports. To examine how jellyfish (Phylum Cnidaria: Orders Semaeostomeae and Rhizostomeae) might drive the broad-scale distribution of this wide ranging species, we employed aerial surveys to map jellyfish throughout a temperate coastal shelf area bordering the northeast Atlantic. Previously unknown, consistent aggregations of Rhizostoma octopus extending over tens of square kilometers were identified in distinct coastal